Nilai-Nilai Pendidikan Islam dalam Hadis la yuqimu ar-rajulu ar-rajula: Islamic Educational Values in the Hadith lā yuqīmu al-rajulu al-rajula: A Textual and Educational Perspective - Maryono; Zaki Ulien Nuha (Prodi PAI, Fakultas Tarbiyah, UNIDA GONTORs Tarbiyah, Universitas Darussalam Gontor, 2025)
This research explains the values of Islamic education in the hadith la yuqimu ar-rajulu ar-rajula. This type of research is library research because the data sources are documents, not direct data from people in their natural environment. The data analysis used is content analysis, research that is an in-depth discussion of the content of written information. Values are beliefs that encourage someone to act based on their choices. Education is the process of guiding and directing the growth and development of students so that they become adult humans in accordance with the goals of Islamic education. The value of Islamic education is the nature or things inherent in Islamic education that humans use to achieve the goal of human life, namely serving Allah. The Hadith of the Prophet Muhammad shallallahu ‘alaihi wa sallam, which includes everything related to the Prophet, whether his words, actions, decrees, characteristics, morals or history, is the source of these values. In this research, the values of Islamic education will be explained in the hadith la yuqimu ar-rajulu ar-rajula. The results of the research found that matters related to Islamic educational values are summarized in 3 educational values, namely i'tiqodiyyah values, khuluqiyyah values, and amaliyyah values. Meanwhile, there are 3 things related to learning material, namely 1) the right to a seat for those who occupy it for the first time, 2) making room for those who have just arrived, and 3) Islam as a very perfect and complete guide to life.